Laser processing of optoelectronic materials - Tan, Bee Sim. (2008)
In this thesis, the objective is to study the effects of KrF excimer (248 nm) laser processing on gallium nitride (GaN) optoelectronic materials. p-GaN and GaN multiple quantum well (MQW) light-emitting diodes (LEDs) which operate in the blue and ultraviolet spectrum were used.